Study of Microstructure of Typical Cervical Vertebrae Pedicle (International Journal of Scientific Research and Management (IJSRM), 2014)
A thorough knowledge of cervical anatomy1 and proficient instrumentation skills are therefore mandatory. The cervical vertebrae are typified by a foramen in each transverse process. The pedicles project posterolaterally. Pedicles are short, thick, rounded dorsal projections from the superior part of the body at the junction of its lateral and dorsal surfaces, so that the concavity formed by its curved superior border is shallower than the inferior one.Study of 5 cadaveric typical (C3-C6) cervical vertebrae pedicles was done on both sides to understand microstructure of pedicles of cervical vertebrae. It was observed that the pedicle cortex was a tubular bone composed of prominent cancellous matrix surrounded by cortical shell. Trabeculae in the cervical pedicles were plate like and isotropic. Cortical bone shell was composed of well-developed lamellar structure lacking proper haversian system. To define the thickness of the medial and lateral cortex, cortical bone was traced along the medial and lateral walls. Medial cortex was observed to be thicker than the lateral cortex. This finding explains the reason for significantly higher frequency of lateral pedicle wall perforation than medial wall perforation during any kind of instrumentation like screw insertion in the region of pedicle. So, for any kind of intervention in the pedicle, direction of the device inserted should be directed medially